Sociologie d’une architecture sans architectes : production de l’espace dans un rassemblement d’habitats mobiles en Arizona - David Frati (Association Internationale des Sociologues de Langue Française, 2021)
This article studies the production of inhabited space in a temporary gathering of elderly people living in mobile dwellings in the Arizona desert, where there are no field of architecture and urban planning involved. We study the effects of socialization on the production of space and formulate the hypothesis that this production of space is a direct expression of inhabitants’ habitus in a context where appropriation of space is at stakes. This article mobilizes tools from fields of both architecture (diagrams, axonometric perspective) and sociology (ethnography, photography), complementary tools to a study of the production of inhabited space from a sociological standpoint.